A study on linguistic features of headlines in English and Vietnamese electronic newspapers / Lý Kiều Hạnh; NHDKH Dr. Nguyễn Thị Vân Đông - Lý, Kiều Hạnh

(untitled)
This thesis is an attempt to deal with the linguistic features of headlines in English and Vietnamese electronic newspapers. To fulfill this objective, the study has conducted to answer four research questions mentioned in chapter III. Qualitative method and Quantitative method are used to analyze the data in terms of syntactic and semantic features. The study makes great effort to point out some similarities and differences between the use of linguistic features of headlines in English and Vietnamese electronic newspapers. From the analysis, syntactic and semantic features of English and Vietnamese headlines are identified and explained. Chapter IV has been carried with great effort to find the similarities and differences between the use of linguistic features of headlines in English and Vietnamese electronic newspapers based on the selected headline samples. Based on the findings, the thesis provides some implications for translators and linguistics to do research on linguistics especially in syntactic and semantic features and gives some suggestions for further research.